Enhanced fractional frequency reuse approach for interference mitigation in femtocell networks - Abdullah H. Alquhali; Mardeni Roslee; Mohamed Babikir Abdelgadir; Khaldon Kordi; Khalid S. Mohamed (Bulletin of Electrical Engineering and Informatics, 2020)
Small cell networks are expected to heavily be deployed in wireless communication networks due to it ability to enhance signals quality and spectrum utilisation. However, interference is posing a major threat to wireless communication especially cellular femtocell networks whereby its performance is degraded in dense deployment areas. For this reason, an enhanced fractional frequency reuse approach is proposed in this paper to mitigate the interference in femtocell networks. This is achieved by dividing the service area and frequency into three regions and three sets whereby each set is allocated different frequency set. The femtocell location is later obtained and assigned frequency in accordance to the region. The proposed approach helps in reducing the interference, boost the signal to interference plus noise (SINR), and enhance the throughput.